2020
DOI: 10.1111/dom.14163
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of polyethylene glycol loxenatide as add‐on to metformin in patients with type 2 diabetes: A multicentre, randomized, double‐blind, placebo‐controlled, phase 3b trial

Abstract: Aim: To assess the efficacy and safety of polyethylene glycol loxenatide (PEX168), a new glucagon-like peptide-1 receptor agonist, as an add-on to metformin therapy in Chinese patients with type 2 diabetes (T2D). Materials and methods: This was a multicentre, randomized, double-blind, placebocontrolled phase 3b trial. After metformin monotherapy (≥1500 mg/day) for 8 weeks or more, patients with uncontrolled T2D (HbA1c of 7.0%-10.5%) from 44 sites were randomized (1:1:1) to metformin + placebo, metformin + PEX1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 34 publications
4
28
0
Order By: Relevance
“…Since there are limited drugs to treat obesity patients and GLP-1RAs have the effect on reducing body weight, it is necessary to study the effect of PEX-168 on weight and blood glucose in simple obesity patients, which can provide relevant data reference for weight loss field. A number of studies have confirmed the safety and efficacy of PEX-168 in patients with T2DM [ 9 , 13 ], while whether PEX-168 can bring a weight loss effect in patients with simple obesity under normal control of blood glucose has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are limited drugs to treat obesity patients and GLP-1RAs have the effect on reducing body weight, it is necessary to study the effect of PEX-168 on weight and blood glucose in simple obesity patients, which can provide relevant data reference for weight loss field. A number of studies have confirmed the safety and efficacy of PEX-168 in patients with T2DM [ 9 , 13 ], while whether PEX-168 can bring a weight loss effect in patients with simple obesity under normal control of blood glucose has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first self-developed long-term GLP-1 RA in China. PEX-168 can avoid the rapid degradation of DPP-4 enzymes and slow down the metabolism of losenatide and prolong the action time in vivo through the modification of polyethylene glycol, so as to improve the efficacy of the drug [ 9 , 10 ]. The clinical recommended dose for adults with diabetes starts from 0.1 mg, and the effective dose in rats starts from 0.03 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…The studies were considered eligible for inclusion if they (1) were randomized clinical trials; (2) were conducted on individuals with type 2 diabetes mellitus; (3) compared GLP-1RAs of interest with each other or with a control group (restricted to placebo or no treatment) with or without the same add-on therapy in all arms; (4) had a follow-up between 24 and 30 weeks; (5) contained results of at least one of the prespecified primary and secondary endpoints; and (6) were published in English language. The final list of included studies was manually supplemented with two studies on loxenatide (Table S4) [14][15][16]. [17].…”
Section: Study Identificationmentioning
confidence: 99%
“…However, research in Jessica and Tina pointed out that further research is still needed to determine the effect of GLP-1 receptor agonists in overweight or obese patients without type 2 diabetes [ 11 , 12 ]. Studies have proven the efficacy and safety of PEX-168 in the treatment of patients with T2DM [ 13 , 14 ], but the effect of PEX-168 on simple obesity and on the regulation of chemerin and omentin expression has not been reported. This study therefore selected six indicators to evaluate the effect of PEX-168 according to prior research and the drug characteristics.…”
Section: Introductionmentioning
confidence: 99%